Effectiveness of conservative urinary incontinence management among female nursing home residents—A cluster RCT. (March 2019) - Hödl, Manuela; Halfens, Ruud J.G.; Lohrmann, Christa
Highlights: UI guideline adherent management increases the likelihood of evidence-based interventions. The intervention can be recommended for nurses/nurse managers. Inclusion of a nurse in recruitment process may increase response rate. Abstract: Background: Guideline-compliant conservative management of urinary incontinence (UI) is the first step of the initial management for UI and is recommended for long-term care in older persons. Recent studies have focused on the effects of guideline-compliant UI management. However, most of these studies were tested in another setting than nursing homes and were not focused on conservative management. Aims: To measure the effectiveness of 29 evidence-based nursing recommendations regarding the conservative management of UI in Austrian nursing homes. Methods: The study is a cluster randomized intervention trial with institution as the unit of randomization. Twelve nursing homes in two Austrian provinces (Styria, Carinthia) were randomly allocated to the intervention group (IG) and control group (CG). Data were collected from participating residents over a three-month period. The intervention consisted of the implementation of recommendations for the conservative management of UI among female nursing home residents. The primary outcome variable was the daily UI experienced by the participating residents. Results: Residents in the (IG n  = 216) had a lower risk (OR = 0.14, p = 0.02) of experiencing daily UI and were less likely to receive absorbent products (OR = 0.01, p = 0.01) than residents in the CG ( n  = 165). Residents in the IG (OR = 5.16, p = 0.00) were five times more likely to receive recommended interventions (e.g., bladder training) than residents in the CG. Conclusion: Introducing guideline-compliant management into nursing practice can increase the likelihood of evidence-based interventions for the conservative management of UI. The intervention in this study targeted on nurses/nurse managers and can be recommended for the nursing home setting.